The effect of vaginal probiotic therapy on the outcome of papillomavirus infection - V. V. Oleynik; E. A. Kremleva; A. V. Sgibnev (Бюллетень сибирской медицины)
Aim. To study the effect of vaginal probiotic therapy on the outcome of human papillomavirus (HPV) infection.Materials and methods. The study included HPV-infected patients: 29 patients with normal vaginal flora and 146 patients with a deficiency of vaginal lactobacilli, of which 117 patients received vaginal probiotic therapy. In samples obtained before and after the therapy, the effect of the probiotic on the change in the ratio of living, apoptotic, and necrotic vaginal epithelial cells after preliminary exposure to oxidative stress was studied.Results. It was found that probiotics reduce the number of infected epithelial cells that survived the oxidative damage and shift the balance of cell death forms towards apoptosis. Vaginal probiotic therapy in patients with a deficiency of lactobacilli increased the frequency of HPV elimination by 2.5 times and reduced the likelihood of treatment failure from 1.5 to 4 times, depending on the viral load. The probiotic therapy made the structure of HPV outcomes in Lactobacillus-deficient patients similar to that in patients with normal vaginal flora.Conclusion. Vaginal probiotic therapy improves outcomes of HPV infection in patients with a deficiency of lactobacilli by reducing the number of survived infected cells and shifting the cell death pattern towards apoptosis.